2010
DOI: 10.4236/ns.2010.210142
|View full text |Cite
|
Sign up to set email alerts
|

Effect of abiotic factors on the molluscicidal activity of oleoresin of Zingiber officinale against the snail Lymnaea acuminata

Abstract: Earlier it has been observed that oleoresin of Zingiber officinale is a potent molluscicide against Lymnaea acuminata. This snail is the vector of Fasciola species, which cause endemic fascioliasis in eastern Uttar Pradesh. As this snail breeds and maintain their population constant through out the year, so that the present study has been designed to find out the effect of variations in some environmental factors in different seasons, on the molluscicidal activity of oleoresin of Zingiber officinale and its re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The reproduction rate was high at 24°C for Pseudosuccinea columella , and this was also observed to tolerate cooler, warmer, and desert temperatures [ 66 ]. However, it was observed that the reproduction rate of Radix acuminata in the tropics occurred optimally at a temperature range of 16–34°C [ 39 , 40 ]. Furthermore, Aziz [ 42 ] and Misra [ 41 ] found that the reproduction rate of Radix luteola (Lamarck) and Radix acuminata , respectively, was higher at lower temperature ranges of 15–20°C.…”
Section: Resultsmentioning
confidence: 99%
“…The reproduction rate was high at 24°C for Pseudosuccinea columella , and this was also observed to tolerate cooler, warmer, and desert temperatures [ 66 ]. However, it was observed that the reproduction rate of Radix acuminata in the tropics occurred optimally at a temperature range of 16–34°C [ 39 , 40 ]. Furthermore, Aziz [ 42 ] and Misra [ 41 ] found that the reproduction rate of Radix luteola (Lamarck) and Radix acuminata , respectively, was higher at lower temperature ranges of 15–20°C.…”
Section: Resultsmentioning
confidence: 99%